The Proteolytic Activity of Philibertia gilliesii Latex : Purification of Philibertain g II - Sequeiros, Cynthia (2016)
The latex from the patagonic plant Philibertia gilliesii Hook. et Arn. (Apocynaceae) is a milky-white suspension containing a proteolytic system constituted by several cysteine endopeptidases. A proteolytic preparation (philibertain g) from the latex of P. gilliesii fruits was obtained and characterized to evaluate its potential use in bioprocesses. Philibertain g contained 1.2 g/L protein and a specific (caseinolytic) activity of 7.0 Ucas/mg protein. It reached 80 % of its maximum caseinolytic activity in the pH 7–10 range, retained 80 % of the original activity after 2 h of incubation at temperatures ranging from 25 to 45 °C and could be fully inactivated after 5 min at 75 °C. Philibertain g retained 60 % of the initial activity even at 1 M NaCl and was able to hydrolyze proteins from stickwater one, of the main waste effluents generated during fishmeal production. Furthermore, as a contribution to the knowledge of the proteolytic system of P. gilliesii, we are reporting the purification of a new peptidase, named philibertain g II (pI 9.4, molecular mass 23,977 Da, N-terminus LPESVDWREKGVVFPXRNQ) isolated from philibertain g through a purification scheme including acetone fractionation, cation exchange, molecular exclusion chromatography, and ultrafiltration.